Measuring the sense of self in brain-damaged patients: A STROBE-compliant article - Hiromitsu, Kentaro (Medicine (Baltimore), 2018)
Recently, researchers have focused on the embodied sense of self (ESS), which consists of the minimal and narrative selves. Although a study demonstrated that the ESS is related to brain dysfunction empirically, the subjective aspects of the ESS, and a systematic approach to it, have not yet been examined in brain-damaged patients. To examine this, we measured the ESS of patients with brain tumors before and after awake craniotomy. A self-reported questionnaire called the Embodied Sense of Self Scale (ESSS) was used to measure the ESS in patients with brain tumors before and after surgery. For comparison, age-matched controls also completed the ESSS. The ESSS scores of the patients with brain tumors before surgery were higher than those of the controls and improved after surgery. Before surgery, patients with left hemispheric lesions had a poorer ESSS than those with right hemispheric lesions. Episodic memory disturbance was highly correlated with malfunction of narrative self and ownership. Brain lesions were associated with anomalous ESSS, associated with hemispheric laterality and cognitive dysfunction.